2005
DOI: 10.1021/jp0581734
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic States in Photosystem II Reaction Center

Abstract: The excited states of a structurally well-determined photosystem II (PSII) reaction center are obtained using an effective Hamiltonian for the interaction between the Q(y) states. The latter are calculated using the time-dependent density functional theory (DFT) method in DFT-optimized geometries, but with conserved side group orientations. Of particular importance is the orientation of the vinyl group of ring I. Couplings are calculated using actual transition charge distributions via the INDO/S model. Good a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 73 publications
0
13
0
Order By: Relevance
“…This was mainly rationalized by the orientation of the vinyl chain. [477] Consequently, it was suggested that the major contribution to the lowest excited state is located at the accessory Chl pigment in branch A. [471,474,478] According to these studies, the second lowest excited state is dominated by the pheophytin residue at branch A.…”
mentioning
confidence: 99%
“…This was mainly rationalized by the orientation of the vinyl chain. [477] Consequently, it was suggested that the major contribution to the lowest excited state is located at the accessory Chl pigment in branch A. [471,474,478] According to these studies, the second lowest excited state is dominated by the pheophytin residue at branch A.…”
mentioning
confidence: 99%
“…Complementing the vast body of experimental work on the RC are various computational studies of the system ( 2 , 5 , 6 , 10 , 13 , 14 , 25 35 ). Early theoretical studies of the PSII RC revealed that there must be some key structural differences between this and the purple bacterial RC.…”
Section: Models Of the Rcmentioning
confidence: 99%
“…This was proven first by the Multimer model ( 2 ), which considered weak excitonic interactions between the majority of RC cofactors and could produce a good approximation of the experimental absorption spectrum despite there being no crystal structure data available at the time. As improvements in the resolution of crystal structures of PSII were published ( 3 , 36 , 37 ), it enabled new models to be built, based upon these parameters ( 13 , 26 28 , 32 , 33 ). These new models incorporated the coupling between pigments ( 32 ) and/or the atomic positions of the pigments themselves ( 13 , 26 , 33 ) as determined from the crystal structure.…”
Section: Models Of the Rcmentioning
confidence: 99%
See 2 more Smart Citations